'What if my experience was not what I expected?': Examining expectation-experience (dis)confirmation effects in China's rural destinations. (October 2021) - Wang, Chaohui; Liu, Juan; Zhang, Tingting
This study (1) compares the tourists' expectation and experience in China's rural destinations, and (2) examines the (dis)confirmation effects of such comparisons on tourists' assessments of overall travel experience, memorability, and authenticity. A total of 1323 valid responses were analyzed to test the proposed model. PLS-SEM results demonstrated that tourists' expectation-experience (dis)confirmation had a main effect on travel experience, memorability, and authenticity. Moreover, the results from pairwise comparisons indicated that, travelers with high expectations and a high-quality experience had the highest evaluation of their overall visit experience, memorability, and authenticity. Whereas, travelers with low expectations and a low-quality experience showed the poorest assessment. Many practical and theoretical implications for destination marketing and management are discussed based on the study's findings.